Autologous noncultured epidermal cell suspension in case of resistant segmental vitiligo: a preliminary study - Hassan, Iffat; Mubashir, Syed; Abdullah, Zubair; Sajad, Peerzada; Anwar, Parvaiz; Sheikh, Gousia; Sami, Abdul; Yaseen, Atiya (Journal of Pakistan Association of Dermatologists, 2016)
Objective To assess the repigmentation efficacy of noncultured epidermal cell suspension (NCECS) in case of resistant segmental vitiligo. Â Patients and methods Three patients having resistant segmental vitiligo were treated with noncultured epidermal cell suspension at the Department of Dermatology, STD & Leprosy, SMHS Hospital (associated teaching hospital of Govt. Medical College, Srinagar) and were followed up for six months. Â Results Two patients showed more than 70% response, one patient more than 50% response. The pattern of pigmentation was uniform and aesthetically acceptable. Â Conclusion Autologous non cultured epidermal cell suspension is one of the best modalities as far as segmental vitiliginous patches resistant to other treatmentÂ modalities are concerned and is one of the novel techniques as far as its outcome is concerned in the form of uniform pigmentation. Â